Aplikasi Expressive Writing Therapy (EWT) pada Ny. SHL dengan Gangguan Persepsi Sensori (Pendengaran) di Ruang Kabela UPTD RSJ Prof. dr. V. L. Ratumbuysang - Pontoh, Novena Paulicia Adventy; Buanasari, Andi; Usman, Suharno (Mapalus Nursing Science Journal, 2024)
Abstract Background. The most common symptom of schizophrenia is hallucinations in the form of sensory responses to unreal stimuli. Without proper treatment, hallucinations can cause sufferers to act out of control. One of the non-pharmacological therapies that can be given is expressive writing therapy. Objective. This study aims to determine the application of Expressive Writing Therapy (EWT) in reducing symptoms of auditory hallucinations. Methods. This study used a case study research design. Data collection was done by interview and observation. The intervention was carried out for 9 days with 7 days of therapy and 2 days of observation. Results: From the intervention results, it was found that Expressive Writing Therapy (EWT) can reduce the auditory hallucination scale from a score of 24 (at pre-test baseline value) to a score of 19 at post-test. Discussion. Hallucinatory symptoms in people with Schizophrenia can be detrimental to sufferers and the surrounding environment in biological, social, and spiritual aspects. Handling hallucinations with Expressive Writing Therapy (EWT) cognitive therapy reduces hallucinations by increasing the ability to control hallucinations in people with schizophrenia and improving self-expression skills. Conclusion. Expressive Writing Therapy (EWT) can be one of the non-pharmacological therapies that can be done as an effort to self-expression and hallucination control in patients with hallucinations.